Walter Pieterse: A Story of Holland - Multatuli, 1820-1887; Evans, Hubert (Salt Lake City, UT : Project Gutenberg, 2009)
"Walter Pieterse: A Story of Holland" by Multatuli is a novel written in the mid-19th century. The narrative follows the young protagonist, Walter Pieterse, as he navigates the challenges of childhood, loves, and society$1 (Bs expectations in Amsterdam. The story highlights his quest for identity and adventure through humorous and poignant observations of his surroundings and the people within them. The opening portion of the work introduces Walter as a contemplative boy in Amsterdam, characterized by both innocent curiosity and a sense of longing for romance and adventure, which he finds through literature. He becomes enamored with a book, (3z(BGlorioso,(3y (Band is caught in a web of social pressures illustrated by his interactions with friends and family. Walter's inner thoughts reveal a rich imagination yearning for a life far removed from the mundane realities of his upbringing, setting the tone for a narrative that explores themes of youth, aspiration, and the impacts of societal norms. The prose is layered with wit and a critical view of social structures, giving readers a nuanced portrayal of life in 19th-century Holland. (This is an automatically generated summary.)s
Release date is 2009-09-29
The Online Distributed Proofreading Team
Keywords: Netherlands -- Fiction